2013
DOI: 10.1364/oe.21.014859
|View full text |Cite
|
Sign up to set email alerts
|

Actively manipulation of operation states in passively pulsed fiber lasers by using graphene saturable absorber on microfiber

Abstract: We experimentally demonstrate an operation switchable Erbium-doped fiber laser by employing graphene saturable absorber (GSA) on microfiber. With the introducing of a polydimethylsiloxane layer, a graphene can be considered as a parallel plate on microfiber and induces different propagation losses to TE and TM modes. By the use of such polarization sensitive GSA on microfiber, Erbium doped fiber laser with switchable operation states such as continuous wave, stable Q-switching, Q-switched mode-locking, and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…Already, micro-fibers and side-polished fibers have been integrated with graphene to achieve improved all-optical modulations, sensors, etc. [14][15][16][17].In this Letter, we integrate graphene layers onto a TFBG to tailor its spectrum and demonstrate a new architecture to strongly enhance fiber sensing in the low-refractive-index region (<1.413). With the interaction between graphene coating and the cladding modes of TFBG, we observe significant changes of the coupling intensity of the cladding modes in TFBG spectrum.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Already, micro-fibers and side-polished fibers have been integrated with graphene to achieve improved all-optical modulations, sensors, etc. [14][15][16][17].In this Letter, we integrate graphene layers onto a TFBG to tailor its spectrum and demonstrate a new architecture to strongly enhance fiber sensing in the low-refractive-index region (<1.413). With the interaction between graphene coating and the cladding modes of TFBG, we observe significant changes of the coupling intensity of the cladding modes in TFBG spectrum.…”
mentioning
confidence: 99%
“…Already, micro-fibers and side-polished fibers have been integrated with graphene to achieve improved all-optical modulations, sensors, etc. [14][15][16][17].…”
mentioning
confidence: 99%
“…However, the switching between continues wave and Q-switched pulse has been demonstrated by using grapheme saturable absorber on microfiber [10]. Therefore, the switching between continuous wave (NMLL) and pulse (MLL) can be realized on a tiny laser system for aerospace navigation in the further.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous reports, both the intraband and interband conductivity are plural forms for TE and TM modes in graphene, and the imaginary portion of which will directly affect the attenuation of two polarization modes [28]. When the chemical potential of graphene is lower, the negative imaginary part of interband conductivity plays a leading role, which results in the improvement of the transmission of TE mode [27][28][29][30]. Since the CVD graphene sandwich the microfiber close in this SSA, sensitive polarization dependence of saturable absorption can be got.…”
Section: Fabrication Characteristic and Polarization Measurement Of mentioning
confidence: 94%
“…The polarization-dependent saturable absorption as shown in Fig. 3 is measured by a home-made mode-locked laser with 1.5 ps pulse at 1.55 µm [27]. We found that the transmission (T TE ) of TE mode of sample A is almost 20.7 times higher than that (T TM ) of the TM mode in the nonsaturable range, which is much larger than sample B (T TE /T TM = 1.9) and C (T TE /T TM = 4.4).…”
Section: Fabrication Characteristic and Polarization Measurement Of mentioning
confidence: 99%